Combined endoscopic approaches to the cardiac sphincter achalasia treatment - V. N. Klimenko; A. M. Kiosov; V. V. Izbitskiy; S. N. Gulevskiy (Zaporožskij Medicinskij Žurnal)
Aim. To assess combined endoscopic approaches to the cardiac sphincter achalasia treatment.